STRATEGIES AND CHALLENGES OF PRE-SERVICE TEACHERS IN THE SEA-TEACHER PROGRAM: A CASE STUDY IN INDONESIA- PHILIPPINE - Fahmi Hidayat; Emma Rosana Febriyanti; Raisa Fadilla (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
The SEA-Teacher Program is a collaborative initiative among Southeast Asian nations, pioneered by SEAMEO, which aims to enhance pre-service teachers’ intercultural competence and teaching skills through cross-cultural practice. The urgency of this research stems from the complex challenges participants face during their placements, such as language barriers, cultural differences, and diverse education systems. These conditions impact learning effectiveness and participant adaptation, necessitating in-depth strategies and reflection to address them. Analyze the specific counter-strategies, coping mechanisms, and support systems employed by the pre-service teachers to effectively navigate and overcome these challenges. Generate practical recommendations and evidence-based strategies derived from these experiences to inform the preparation of future participants, enhance program design for educators and policymakers, and strengthen regional collaboration in teacher education. Highlight the lessons learned and best practices developed by the participants in promoting adaptability, resilience, and problem-solving skills, thereby contributing to their professional and personal transformation into effective future teachers. The study method employed is a qualitative approach with reflective analysis. Data were gathered through interviews, teaching practice reports, and participant reflection notes. The analysis is focused on identifying intercultural, linguistic, and pedagogical challenges, as well as the adaptation strategies used, such as collaboration with local teachers, modification of teaching methods, and the utilization of cultural experiences.